# math

*if it is in parentheses, it is subscripted.

the sequence {a(n)} is defined recursively by a(1) = 1, a(2) = 1 and for all n>= 1, a(n+2) = a(n+1) + a(n). use the principle of mathematical induction to prove that a(1) + a(2) + a(3) + ... + a(n) = a(n+2) - 1

1. 👍 0
2. 👎 0
3. 👁 29

## Similar Questions

1. ### Math

this is a difficult question for me please help! thankyou A sequence is defined recursively by an + 1 = 3an − n, a1 = 2. Find the first six terms of the sequence. a1 = a2 = a3 = a4 = a5 = a6 =

asked by lene on August 15, 2015
2. ### math asap

this is a difficult question for me please help! thankyou A sequence is defined recursively by an + 1 = 3an − n, a1 = 2. Find the first six terms of the sequence. a1 = a2 = a3 = a4 = a5 = a6 =

asked by lene on August 15, 2015
3. ### algebra 2

A sequence is defined recursively by a1=1,an=(an-1+1)^2. Write the first 4 terms of the sequence.

asked by jenny on May 23, 2012
4. ### Math Help

Hi! I need help with these two questions. Thanks! 1.) Look for the first four terms for the following sequence below. an=n(n^2-6) 2.) For this question, remember that your answer has to begin with the second term of the following

asked by Tori on April 29, 2015
5. ### Discrete Math

Calculate R(4) where the recursively defined sequence R is given by: R(1) = 2, R(2) = 3, and, R(n) = R(n − 1) + 2R(n − 2) + n, n > 2

asked by Ashley Everette on April 15, 2010
6. ### Math

The Fibonacci sequence, (fn) n∈N, is defined recursively as follows: f0 = f1 = 1, fn = fn-2 + fn-1 (n ≥ 2) Demonstrate for all n ∈ N: If n ≥ 1, then fn-1 ⋅fn + 1 = f ^ 2n - (- 1) ^ n .

asked by Michelle on September 5, 2018
7. ### pre algebra

what is the first five terms of the the following recursively defined sequence with the steps please. a=1;=3a

asked by mikey on November 1, 2017
8. ### Algebra 2

Create an explicit equation for each recursively defined sequence below a1=17,an+1=an-7

asked by Eric on October 13, 2015
9. ### precalculus

Find the first five terms of the given recursively defined sequence. an = 3an − 1 + 9 and a1 = 2

asked by Ama on November 22, 2012
10. ### Urgent math

Find the first five terms of the given recursively defined sequence. an = 3an − 1 + 6 and a1 = 1 a1= a2= a3= a4= a5=

asked by Fay on August 10, 2015

More Similar Questions